Financial Well-Being of Mature and Elderly People In The Visegrad Group Countries - Ewa SOBOLEWSKA-PONIEDZIAŁEK (Communications of International Proceedings, 2022)
The demographic changes taking place on the European continent are of a very dynamic nature, which requires that they be analysed both in the context of causes as well as possible consequences. The scope of the analysis of this study will primarily consider the consequences of changes within the age structure of the population, as a result of which the share of older people in the total population increases. This, in turn, implies the fact that the socio-economic consequences of demographic changes may, on the one hand, constitute a development barrier, and offer an opportunity for the development of new branches in the economy, on the other. The growing share of mature and elderly people in the general structure of the population combined with the growing purchasing power of these consumers may inspire and trigger the emergence of new industries and market segments focused on creating an offer meeting the needs of older people. The aim of this article is to analyze the financial well-being of people on the verge of old age and the elderly as a factor influencing the quality of life. The situation of older Poles compared to the situation of citizens of the countries associated in the Visegrad group (V4) will be subject to comparative analysis.
Keywords: financial well-being; the elderly; standard of living; income inequalities